KOMITMEN GURU YANG DISERTIFIKASI DALAM MELAKSANAKAN TUGAS DI SMK NEGERI KELOMPOK BISNIS MANAJEMEN KOTA PADANG - Wina Canigia (Universitas Negeri Padang, 2014)
The goal of this research are to see information about the Commitment of Teachers Sertification To Carry Out The Task. The population is 100 teachers sertification and the sample is 80 people that taken by Simple Random Sampling. The instrument of this research is question with Likert scale models that had tested for validity and realibility. Data analyzed using mean score and performance level. The result of this research are the Commitment Of Teachers Sertification To Carry Out The Task In SMK State Kelompok Bisnis Manajemen Kota Padang stay in good enough category. Key word : Commitmen Teachers of Sertification